The resilient founder : lessons in endurance from startup entrepreneurs - Ramsinghani, Mahendra (John Wiley & Sons, Inc., 2022)
"This book which can be presented as a "Rough Guide to Emotional Resilience" addresses the unspoken challenges of a business leader's journey. Business leaders often struggle with dark nights and suffer from anxiety, depression, and possible mental breakdowns. The author will help readers to identify early warnings, offers tools and techniques to build their endurance, the ability to be vulnerable yet stay resilient. Most importantly, this book draws lessons of endurance from over hundred company founders and how they wrestled with their emotional demons. In a world where passion is the overblown fetish, bravado and chutzpah is the currency of champions, and emotions are buried deep, this book offers strength, solace, and guidance to those who endure the long game"--